BLUE OCEAN STRATEGY (BOS): ALTERNATIVE STRATEGY FOR MANAGEMENT DEVELOPMENT IN ISLAMIC EDUCATIONAL INSTITUTIONS - Sari, Sri Yulia; Triani, Lidya; Purnama, Meira Dwi Indah (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2023)
The focus of this article is to describe Blue Ocean Strategy (BOS] or Blue ocean Strategy as a new strategy model in the management of Islamic education institutions. The author seeks to describe the adoption of the world's blue ocean strategy into the world of education and answers what principles are accepted and rejected from theory . Adoption of the Blue Ocean strategy or a blue ocean strategy implemented by applying universal principles .Prinsip Blue Ocean strategy to be adopted by both are indicators that focus provide excellent service to consumers while indicators that can not be adopted is a strong indicator of economic motivations ( commercialization). Generally the Blue Ocean Strategy can be applied quite well and can be used as an alternative to the development of management of Islamic education institutions.